2013
DOI: 10.1097/brs.0b013e3182a0d264
|View full text |Cite
|
Sign up to set email alerts
|

New, Clinically More Relevant Model for Nerve Root Injury in the Rat

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The newly developed rat model used in this study has been shown to increase spontaneous pain-related behavior [4], but studies specifically evaluating hyperalgesia have not yet been conducted, which is a limitation when comparing our results with others. Nevertheless, we believe this is the most clinically relevant model available, because the needle induces mechanical deformation of the clinically most commonly affected structure (the nerve root) [4].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…The newly developed rat model used in this study has been shown to increase spontaneous pain-related behavior [4], but studies specifically evaluating hyperalgesia have not yet been conducted, which is a limitation when comparing our results with others. Nevertheless, we believe this is the most clinically relevant model available, because the needle induces mechanical deformation of the clinically most commonly affected structure (the nerve root) [4].…”
Section: Discussionmentioning
confidence: 52%
“…In this pilot study, we found a downregulation of the Htr2c gene in experimental disc herniation in the rat that was reduced by TNF inhibition. This suggests that changes in serotonergic transmission may contribute to the changes in spontaneous pain behavior previously observed in this model [4], shedding further light on the complex pathophysiology of disc herniation and sciatica.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations